Influenza vaccination among pregnant women in two hospitals in Sydney, NSW: what we can learn from women who decline vaccination - Jocelynne E McRae; Aditi Dey; Samantha Carlson; John Sinn; Peter McIntyre; Frank Beard; Kristine Macartney; Nicholas Wood (Public Health Research & Practice, 2022)
Objective: Pregnant women are recognised as being at risk of serious illness from influenza. Despite this, and longstanding national recommendations for vaccination in pregnancy, vaccine uptake remains suboptimal. This study aims to determine factors associated with women declining influenza vaccination in pregnancy.